Impact of tumour bed boost integration on acute and late toxicity in patients with breast cancer: A systematic review. (June 2016) - Hamilton, Daniel George; Bale, Rebecca; Jones, Claire; Fitzgerald, Emma; Khor, Richard; Knight, Kellie; Wasiak, Jason
Abstract: The purpose of this systematic review was to summarise the evidence from studies investigating the integration of tumour bed boosts into whole breast irradiation for patients with Stage 0-III breast cancer, with a focus on its impact on acute and late toxicities. A comprehensive systematic electronic search through the Ovid MEDLINE, EMBASE and PubMed databases from January 2000 to January 2015 was conducted. Studies were considered eligible if they investigated the efficacy of hypo- or normofractionated whole breast irradiation with the inclusion of a daily concurrent boost. The primary outcomes of interest were the degree of observed acute and late toxicity following radiotherapy treatment. Methodological quality assessment was performed on all included studies using either the Newcastle–Ottawa Scale or a previously published investigator-derived quality instrument. The search identified 35 articles, of which 17 satisfied our eligibility criteria. Thirteen and eleven studies reported on acute and late toxicities respectively. Grade 3 acute skin toxicity ranged from 1 to 7% whilst moderate to severe fibrosis and telangiectasia were both limited to 9%. Reported toxicity profiles were comparable to historical data at similar time-points. Studies investigating the delivery of concurrent boosts with whole breast radiotherapy courses report safe short to medium-term toxicity profiles and cosmesis rates. Whilst the quality of evidence and length of follow-up supporting these findings is low, sufficient evidence has been generated to consider concurrent boost techniques as an alternative to conventional sequential techniques. Highlights: First systematic review to assess breast toxicity with concurrent boost regimes. 35 studies have assessed concurrent tumour bed boost strategies between 2000 and 2015. 10 of the 17 included studies were case series (Level IV) and evaluated as "poor". Fifteen different radiation dose prescriptions were evaluated. Concurrent boosts demonstrate non-inferior short and medium toxicity profiles.